Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

[tex]\[
\begin{array}{l}
\frac{x-2}{3}+\frac{y+1}{6}=2 \\
\therefore \frac{x-3}{4}-\frac{2y-1}{2}=1
\end{array}
\][/tex]

Solve for [tex]\(x\)[/tex] and [tex]\(y\)[/tex].


Sagot :

To solve the given system of equations, we need to follow several steps to find the values of \( x \) and \( y \).

### Step 1: Write the System of Equations

The system of equations given is:

[tex]\[ \frac{x-2}{3} + \frac{y+1}{6} = 2 \][/tex]

[tex]\[ \frac{x-3}{4} - \frac{2y-1}{2} = 1 \][/tex]

### Step 2: Simplify the Equations

Let's clear the fractions to make the equations easier to work with.

For the first equation, multiply every term by the least common multiple (LCM) of the denominators, which is 6:

[tex]\[ 6 \left( \frac{x-2}{3} \right) + 6 \left( \frac{y+1}{6} \right) = 6 \cdot 2 \][/tex]

[tex]\[ 2(x - 2) + (y + 1) = 12 \][/tex]

[tex]\[ 2x - 4 + y + 1 = 12 \][/tex]

[tex]\[ 2x + y - 3 = 12 \][/tex]

[tex]\[ 2x + y = 15 \quad \text{(Equation 1)} \][/tex]

For the second equation, multiply every term by the LCM of the denominators, which is 4:

[tex]\[ 4 \left( \frac{x-3}{4} \right) - 4 \left( \frac{2y-1}{2} \right) = 4 \cdot 1 \][/tex]

[tex]\[ x - 3 - 2(2y - 1) = 4 \][/tex]

[tex]\[ x - 3 - 4y + 2 = 4 \][/tex]

[tex]\[ x - 4y - 1 = 4 \][/tex]

[tex]\[ x - 4y = 5 \quad \text{(Equation 2)} \][/tex]

### Step 3: Solve the System of Linear Equations

We now have:

[tex]\[ 2x + y = 15 \quad \text{(Equation 1)} \][/tex]

[tex]\[ x - 4y = 5 \quad \text{(Equation 2)} \][/tex]

First, let's solve Equation 2 for \( x \):

[tex]\[ x = 4y + 5 \][/tex]

Now, substitute \( x = 4y + 5 \) into Equation 1:

[tex]\[ 2(4y + 5) + y = 15 \][/tex]

[tex]\[ 8y + 10 + y = 15 \][/tex]

[tex]\[ 9y + 10 = 15 \][/tex]

[tex]\[ 9y = 5 \][/tex]

[tex]\[ y = \frac{5}{9} \][/tex]

### Step 4: Substitute \( y \) back into the Equation for \( x \)

Substitute \( y = \frac{5}{9} \) back into the equation \( x = 4y + 5 \):

[tex]\[ x = 4 \left( \frac{5}{9} \right) + 5 \][/tex]

[tex]\[ x = \frac{20}{9} + 5 \][/tex]

Convert the 5 to a fraction:

[tex]\[ x = \frac{20}{9} + \frac{45}{9} \][/tex]

[tex]\[ x = \frac{65}{9} \][/tex]

### Step 5: Write the Solution

The solution to the system of equations is:

[tex]\[ x = \frac{65}{9}, \quad y = \frac{5}{9} \][/tex]

Therefore, the values of \( x \) and \( y \) are:

[tex]\[ \boxed{\left( \frac{65}{9}, \frac{5}{9} \right)} \][/tex]